Autonomous operation of ac–dc microgrids with minimised interlinking energy flow. Issue 8 (1st September 2013) - Loh, Poh Chiang; Li, Ding; Chai, Yi Kang; Blaabjerg, Frede
Abstract : Modern distributed sources can either be ac or dc. It is thus possible to form hybrid microgrids with both ac and dc sub‐grids inter‐tied by power converters. The resulting hybrid architecture allows loads to be flexibly placed, hence reducing the amount of power conversion needed. Hybrid microgrids can therefore be more efficient if controlled appropriately. For that, a droop scheme is now proposed for coordinating energy flows within the hybrid microgrids. The scheme operates autonomously and efficiently without demanding for fast communication links. The overall energy flow tuning and hybrid microgrids have already been tested in experiments.